2023
DOI: 10.1111/ajco.13915
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity profile of patients treated with proton and carbon‐ion therapy for primary nasopharyngeal carcinoma: A systematic review and meta‐analysis

Abstract: BackgroundProton and carbon‐ion therapy may spare normal tissues in regions with many critical structures surrounding the target volume. As toxicity outcome data are emerging, we aimed to synthesize the published data for the toxicity outcomes of proton or carbon‐ion therapy (together known as particle beam therapy [PBT]) for primary nasopharyngeal carcinoma (NPC).Materials and methodsWe searched PubMed and Scopus electronic databases to identify original studies reporting toxicity outcomes following PBT of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been observed that the incidence of coronary events increases by 7.4 per 1 Gy increase in the mean heart dose [33]. In most studies, hybrid techniques (H-VMAT, H-IMRT) had lower heart doses than VMAT or IMRT [13][14][15][16][17][18]20], but some studies reported no statistically significant difference [25,27]. However, these latter studies included both breast and chest wall patients, which could affect the final result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been observed that the incidence of coronary events increases by 7.4 per 1 Gy increase in the mean heart dose [33]. In most studies, hybrid techniques (H-VMAT, H-IMRT) had lower heart doses than VMAT or IMRT [13][14][15][16][17][18]20], but some studies reported no statistically significant difference [25,27]. However, these latter studies included both breast and chest wall patients, which could affect the final result.…”
Section: Discussionmentioning
confidence: 99%
“…The search was conducted in the PubMed and Scopus databases using the population, intervention, control, and outcomes (PICO) framework to establish the search terms (Table 1, Appendix). This type of review is widely used to expand upon the current knowledge base to drive the development of healthcare practice [16][17][18]. Boolean search phrase combinations were used to guarantee that all pertinent articles were found (Supplementary A).…”
Section: Review Materials and Methodsmentioning
confidence: 99%
“…For instance, the peculiar dose distribution of protons leads to a significant reduction in the low "dose bath" absorbed by surrounding healthy tissues that are typically seen in photon-based techniques like intensity-modulated radiotherapy (IMRT). This could result in several advantages, like reducing (1) acute and late treatment-related side effects, (2) radiationinduced secondary-cancer risk (mainly in young patients), and (3) immune system depression (thanks to the lower exposure of circulating lymphocytes and immune organs like lymph nodes) [5][6][7][8][9][10][11][12]. Moreover, technological advances have allowed the transition from passive scattering to pencil-beam scanning (PBS), with even higher conformity of the dose distribution-a technique routinely introduced by the Paul Scherrer Institute (Villigen, Switzerland) in the late 1990s.…”
Section: Introductionmentioning
confidence: 99%
“…Proton therapy (PT) offers several advantages over photon therapy, including the elimination of exit dose and the possibility to tailor the dose resulting from the physical characteristics of the beams with Bragg peaks [ 10 ]. Several dose comparisons and clinical studies have shown significant normal tissue dose reductions favoring PT [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%